Implementasi Pemberian Cuti Mengunjungi Keluarga bagi Narapidana berdasarkan PERMENKUMHAM Nomor 16 Tahun 2023 : (Studi di Lembaga Pemasyarakatan Kelas II B Gunung Sugih) - Baharudin Baharudin; Dimas Ferdian (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The Family Visiting Leave Programme at Class II B Gunung Sugih Correctional Facility faces obstacles due to the imbalance between the number of officers and the workload that must be handled. In addition, limited facilities and lack of supporting facilities in prisons also hamper the effectiveness of the implementation of this programme. This research aims to analyse the implementation of Family Visiting Leave for prisoners in Class II B Gunung Sugih Correctional Facility and the obstacles faced based on Permenkumham Number 16 of 2023. This research uses a normative juridical approach through literature study and document analysis, as well as an empirical approach through observation and interviews. The data was analysed using qualitative juridical methods to draw conclusions based on empirical findings in the field. The results of this study indicate that the provision of Family Visiting Leave at Class II B Gunung Sugih Correctional Facility is given to prisoners who have shown good behaviour and have served at least half the criminal period, as part of an effort to encourage social reintegration. However, the programme faces a number of obstacles, including internal issues such as the low quality of human resources (HR) and overcrowding that hamper the effectiveness of its implementation. In addition, there are external obstacles that include negative stigma from the community as well as a lack of cooperation between the prison and related agencies, which affect the success of the programme.